2022
DOI: 10.3390/genes13081355
|View full text |Cite
|
Sign up to set email alerts
|

A Rare MSH2 Variant as a Candidate Marker for Lynch Syndrome II Screening in Tunisia: A Case of Diffuse Gastric Carcinoma

Abstract: Several syndromic forms of digestive cancers are known to predispose to early-onset gastric tumors such as Hereditary Diffuse Gastric Cancer (HDGC) and Lynch Syndrome (LS). LSII is an extracolonic cancer syndrome characterized by a tumor spectrum including gastric cancer (GC). In the current work, our main aim was to identify the mutational spectrum underlying the genetic predisposition to diffuse gastric tumors occurring in a Tunisian family suspected of both HDGC and LS II syndromes. We selected the index ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
2
2
0
Order By: Relevance
“…This in-frame deletion is located in the exon 4 of CHEK2 gene and predicted to lead to the loss of two amino acids, Among the selected variants, c.728G>A in MSH2 gene was identified in one breast cancer case with a family history of ovarian, gastric and lung cancers. Interestingly, this same variant was recently described in a Tunisian patient with gastric cancer that has a family history of breast, ovarian, and colon cancers (Kabbage et al, 2022). In this same study, structural bioinformatics analyses revealed that this variant is involved in the MSH2-MLH1 complex stability and may impact on the binding of MSH2 protein with MLH1 by disrupting the electrostatic potential which is suggestive of a pathogenic effect.…”
Section: Genotype Phenotype Correlation and Segregation Analysissupporting
confidence: 61%
See 3 more Smart Citations
“…This in-frame deletion is located in the exon 4 of CHEK2 gene and predicted to lead to the loss of two amino acids, Among the selected variants, c.728G>A in MSH2 gene was identified in one breast cancer case with a family history of ovarian, gastric and lung cancers. Interestingly, this same variant was recently described in a Tunisian patient with gastric cancer that has a family history of breast, ovarian, and colon cancers (Kabbage et al, 2022). In this same study, structural bioinformatics analyses revealed that this variant is involved in the MSH2-MLH1 complex stability and may impact on the binding of MSH2 protein with MLH1 by disrupting the electrostatic potential which is suggestive of a pathogenic effect.…”
Section: Genotype Phenotype Correlation and Segregation Analysissupporting
confidence: 61%
“…Indeed, this variant, which was described in a gastric cancer patient, appears to affect the MSH2-MLH1 complex as well as DNAcomplex stability. Interestingly, both cases carrying this variant (current report & Kabbage et al, 2022) showed family history of cancer suggestive of lynch syndrome involving breast, gastric and ovarian malignancies which in turn may support the pathogenicity of the c.728G>A variant. In addition to MMR genes, we have identified a likely pathogenic splicing variant in RAD50 gene that was predicted to lead to exon skipping (c.3036+5G>A).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations